On The Shift to Decentralised Identity Management in Distributed Data Exchange Systems - Bakhtina, Mariia (2023)
The commonly used centralised trust and centralised identity man agement make information systems and organisations prone to a single point of failure. Therefore, decentralised identity man agement has appeared as an alternative solution to mitigate the weaknesses of centralised identity. In this paper, we propose an approach of system analysis that should guide organisations that considers the transition to decentralised identity management. The approach aims to support decision-making about the usefulness of the transition based on the created assessment model. The approach is validated through a case study of the X-Road ecosystem.